Noncanonical NF‐κB Signaling Regulates Hematopoietic Stem Cell Self‐Renewal and Microenvironment Interactions123. (22nd March 2012) - Zhao, Chen; Xiu, Yan; Ashton, John; Xing, Lianping; Morita, Yoshikazu; Jordan, Craig T.; Boyce, Brendan F.
Abstract: RelB and nuclear factor κB (NF‐κB2) are the main effectors of NF‐κB noncanonical signaling and play critical roles in many physiological processes. However, their role in hematopoietic stem/progenitor cell (HSPC) maintenance has not been characterized. To investigate this, we generated RelB/NF‐κB2 double‐knockout (dKO) mice and found that dKO HSPCs have profoundly impaired engraftment and self‐renewal activity after transplantation into wild‐type recipients. Transplantation of wild‐type bone marrow cells into dKO mice to assess the role of the dKO microenvironment showed that wild‐type HSPCs cycled more rapidly, were more abundant, and had developmental aberrancies: increased myeloid and decreased lymphoid lineages, similar to dKO HSPCs. Notably, when these wild‐type cells were returned to normal hosts, these phenotypic changes were reversed, indicating a potent but transient phenotype conferred by the dKO microenvironment. However, dKO bone marrow stromal cell numbers were reduced, and bone‐lining niche cells supported less HSPC expansion than controls. Furthermore, increased dKO HSPC proliferation was associated with impaired expression of niche adhesion molecules by bone‐lining cells and increased inflammatory cytokine expression by bone marrow cells. Thus, RelB/NF‐κB2 signaling positively and intrinsically regulates HSPC self‐renewal and maintains stromal/osteoblastic niches and negatively and extrinsically regulates HSPC expansion and lineage commitment through the marrow microenvironment. STEM CELLS 2012; 30:709–718